2015
DOI: 10.1299/mel.15-00350
|View full text |Cite
|
Sign up to set email alerts
|

Geometric features of MnS grains in damaged free-cutting steel SUM24L by fatigue and dynamic tension

Abstract: For free-cutting steels, their mechanical properties, especially local toughness, are functionally degraded. The second phase exists in steel matrix, as a chip breaker, tool edge stabilizer and tool life extender. For these purposes, the second phase plays the role of a solid lubricant. Typical materials as the second phase in free-cutting steels are Pb and MnS. The second phase grains are recognized as stress concentrated points during machining. Such points have the possibility to be new crack initiation sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…The pre-fatigue loading expected to accelerate the degradation due to the change of interfacial situation between steel matrix and the second phase, mainly MnS grain. Itabashi and Koseki (2013) reported low-cycle pre-fatigue gave 10% reduction of quasistatic strength and 20% reduction of dynamic one, for the same lot steels of this series of experiments. As explained earlier, the maximum (pre-fatigue) stress of 100 MPa was almost the onset of the degradation.…”
Section: Effect Of the Pre-fatigue On Stress-strain Curvesupporting
confidence: 66%
See 1 more Smart Citation
“…The pre-fatigue loading expected to accelerate the degradation due to the change of interfacial situation between steel matrix and the second phase, mainly MnS grain. Itabashi and Koseki (2013) reported low-cycle pre-fatigue gave 10% reduction of quasistatic strength and 20% reduction of dynamic one, for the same lot steels of this series of experiments. As explained earlier, the maximum (pre-fatigue) stress of 100 MPa was almost the onset of the degradation.…”
Section: Effect Of the Pre-fatigue On Stress-strain Curvesupporting
confidence: 66%
“…After tensile fracture, the number of such penetrations drastically increased, because transverse compression was induced during necking formation. Formerly, the present author thought that this phenomenon could be utilized for the indicator of loading history of fractured free-cutting steel (Itabashi, 2015).…”
Section: Introductionmentioning
confidence: 93%
“…Depending on the previous work on the subject in question, the effect of prefatigue on stress-strain properties may vary depending on the material type and fatigue loading parameters. For example, alloy hardening was found for 2017A-T3 [4] , followed by material softening, and for AISI 4140T [3] , Softening only occurs in AISI 1215 and AISI 12L14 [6] steels, while the above characteristics are absent in 5544-O [4] and 6061-T6 [3] alloys. In addition, the development of fatigue damage may lead to a significant decrease in fracture strain [5] .…”
Section: Introductionmentioning
confidence: 98%
“…The microstructure of pre-fatigue specimens is affected by cyclic softening or hardening effect and microscopic damage. Studies conducted in this area have clearly shown that due to previous cyclic loading, the elongation of 6061-T6 aluminum alloy decreased by 9%, AISI 4140T steel decreased by 63% [3] , 2017A-T3 aluminum alloy decreased by 70%, and 5544-O alloy decreased by 6% [4] , The decrease was 60% for Ti-6Al-4V titanium alloy [5] , 4% for AISI 1215 steel and 10% for AISI 12L14 steel [6] . Depending on the previous work on the subject in question, the effect of prefatigue on stress-strain properties may vary depending on the material type and fatigue loading parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Free-machining steels containing sulfur and lead are widely used for production of precision small parts machined by various metalworking equipment, especially automatic turning lathes and barstock machines [1][2][3][4][5][6]. But the tendency for limitation of environmentally harmful substances is growing, and modern regulations restrict the use of heavy metals including lead [7][8][9][10]. Producers of automobiles and office devices carry out intensive research to replace lead-bearing steels presently in use with new lead-free steels having in view the expected further restriction of environmental norms.…”
Section: Introductionmentioning
confidence: 99%